Developing Donor Relationships: The Role of the Breadth of Giving - Khodakarami, Farnoosh; Petersen, J. Andrew; Venkatesan, Rajkumar (Journal of Marketing, 2015)
This research proposes a mechanism to develop long-term donor relationships, a major challenge in the nonprofit industry. The authors propose a metric, donation variety, which captures a donor's breadth of donations with a given nonprofit organization, controlling for the distribution of donations to different initiatives. Using donation data spanning 20 years from a major U.S. public university, the authors find that improvements in donation variety increase the likelihood that the donor will make a subsequent donation, increase the donation amount, and reduce the sensitivity of donations to negative macroeconomic shocks. In the acquisition phase, most donors give to a single initiative, and these decisions are more influenced by a donor's intrinsic motivations. In contrast, as the donor–nonprofit organization relationship develops over time, nonprofit marketing efforts have a more significant influence on a donor's decision to give to multiple initiatives. Finally, the authors conduct a field study that validates the econometric analysis and provides causal evidence that marketing efforts by nonprofit organizations can encourage donors to spread donations across multiple initiatives.